2007
DOI: 10.1158/1541-7786.mcr-06-0286
|View full text |Cite
|
Sign up to set email alerts
|

HAb18G/CD147 Functions in Invasion and Metastasis of Hepatocellular Carcinoma

Abstract: CD147 molecule is reported to be correlated with the malignancy of some cancers; however, it remains unclear whether it is involved in the progression of hepatocellular carcinoma (HCC). Here, we investigated the function of HAb18G/CD147, a member of CD147 family, and its antibodies, HAb18 and LICARTIN, in HCC invasion and metastasis. We observed that HAb18G/CD147 gene silence in HCC cells significantly decreased the secretion of matrix metalloproteinase (MMP) and the invasive potential of HCC cells (P < 0.001)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
134
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 144 publications
(140 citation statements)
references
References 31 publications
4
134
0
Order By: Relevance
“…CD147, a glycosylated immunoglobulin super family transmembrane protein, is highly expressed by HCC cells. Several in vitro studies suggest that CD147 promotes tumor invasion and metastasis, (18)(19)(20) inhibits apoptosis (21) and anoikis,promotes tumor angiogenesis, (23,24) and confers resistance to some chemotherapeutic drugs.(22) These findings indicate that CD147 might be a chemotherapeutic target for treating hepatoma. Our previous study shows that CD147 might play an important role in the inhibitory regulation of autophagy and autophagic cell death in HCC cells; (25) however, whether CD147 also plays a role in mediating the anticancer effects of berberine remains unclear.…”
mentioning
confidence: 99%
“…CD147, a glycosylated immunoglobulin super family transmembrane protein, is highly expressed by HCC cells. Several in vitro studies suggest that CD147 promotes tumor invasion and metastasis, (18)(19)(20) inhibits apoptosis (21) and anoikis,promotes tumor angiogenesis, (23,24) and confers resistance to some chemotherapeutic drugs.(22) These findings indicate that CD147 might be a chemotherapeutic target for treating hepatoma. Our previous study shows that CD147 might play an important role in the inhibitory regulation of autophagy and autophagic cell death in HCC cells; (25) however, whether CD147 also plays a role in mediating the anticancer effects of berberine remains unclear.…”
mentioning
confidence: 99%
“…Interestingly, there is an established relationship between CD147 protein levels and hepatocarcinoma progression. Overexpression of HG-CD147 enhances the invasive ability of Hepa1-6 cells (24), and CD147 gene silence in hepatocellular carcinoma (HCC) cells significantly decreases the secretion of MMP and the invasive potential of HCC cells (25). CD147 also serves potentially as a pathological target for cancer detection of early hepatocarcinoma (26).…”
Section: Discussionmentioning
confidence: 99%
“…As a member of the immunoglobulin superfamily, CD147 is overexpressed in a number of epithelial cell-derived carcinomas and is associated with tumor development (20)(21)(22)(23). In previous studies, we demonstrated that the interaction of HAb18G/CD147 with integrin b1 activates the downstream FAK/PI3K-Akt signaling pathway, subsequently enhancing the malignant properties and inhibiting the chemosensitivity of HCC cells (24,25).…”
Section: Introductionmentioning
confidence: 86%